EXPERIMENTAL STUDY OF FATIGUE CRACK GROWTH FOR PMMA - CHEN XiaoGang; WEI Bing; HUI ZhanRong (Jixie qiangdu)
Polymethyl Mechacry（ PMMA） has been widely used in aircraft structures such as windscreen and cockpit canopy because of its excellent performance of strength and transparence. The capacity of its resistance to crack growth is important to the service life and safety of the aircraft. The crack growth rate of three different PMMA has been tested using the CCT specimens. The tested data was dealt with seven point incremental polynomial method to compute the relationship between crack growth rate and range of stress intensity factor under various test conditions. The influence of stress ratio and residual stress has been analyzed. The experimental results provides the basis and reference to the selection,utilization and maintenance of PMMA for the aircraft.